Damping Enhancement in Multimachine Power Systems via Output Feedback Excitation Controller - syah, Hardian (Faculty of Engineering, Universitas Tanjungpura, 2011)
Abstract This paper presents an output feedback controller to damp the electromechanical oscillations in multimachine power systems. The control design is based on a modified optimal controller which it does not need the specification of weighting matrices. The eigenvalues of electromechanical modes would be shifted to a pre-specified vertical strip. Effectiveness of this controller is evaluated and example, a multimachine power system, is given to illustrate the advantages and effectiveness of the proposed method. Keywords - dynamic stability, strip eigenvalue assignment, output feedback controller